Effects of BAC-filtration, disinfection, and temperature on water quality in simulated reclaimed water distribution systems. Issue 11 (24th September 2020) - Zhu, Ni; Ghosh, Sudeshna; Strom, Laurel; Pruden, Amy; Edwards, Marc A.
Abstract : The distinct characteristics of reclaimed versus potable water have important implications for design and operation of reclaimed water distribution systems (RWDSs). Abstract : The distinct characteristics of reclaimed versus potable water have important implications for design and operation of reclaimed water distribution systems (RWDSs). Here we operated six simulated RWDSs in parallel to determine the effects of feed water treatment (with and without biologically-active carbon (BAC) filtration) and residual disinfectants (chlorine, chloramine, or no residual) on the distributed water quality. Following a six-month acclimation period, the experimental conditions were implemented over 2 years of operation, with a temperature regime of 14 °C → 22 °C → 30 °C → 22 °C → 14 °C imposed to simulate seasonal variation. Comprehensive water chemistry profiling and microbial sampling were conducted over a range of water ages (0 d, 1 d, 2.5 d and 5 d) along the RWDSs at each temperature phase. When ≥22 °C, RWDSs became more vulnerable to deterioration of water quality due to nitrification, as evidenced by accelerated chloramine decay and increased relative abundance of nitrifier genera and functional genes. Contrary to conventional experience in potable water distribution, chlorine generally became more persistent than chloramine from the first 22 °C phase onwards. Enhanced persistence of chlorine was accompanied by increased biological stability ( i.e., lower cell counts and reduced dissolved oxygen demand). BAC filtration initially improved water quality ( i.e., lower total organic carbon and biomass, longer persistence of disinfectants), but benefits diminished over long term distribution system operation. Taxonomic and functional metagenomic profiles revealed that chlorine had the strongest selective effect compared to both chloramine and no residual, particularly for the unfiltered condition. The long-term operation strategy employed here enabled evaluation of distribution system management practices and their interactive effects as the RWDSs experienced temperature shifts and aged.